Effects of density gradients and fluctuations at the plasma edge on ECEI measurements at ASDEX Upgrade. (8th February 2018) - Vanovac, B; Wolfrum, E; Denk, S S; Mink, F; Laggner, F M; Birkenmeier, G; Willensdorfer, M; Viezzer, E; Hoelzl, M; Freethy, S J; Dunne, M G; Lessig, A; et al.
Abstract: Electron cyclotron emission imaging (ECEI) provides measurements of electron temperature ( T e ) and its fluctuations ( δT e ). However, when measuring at the plasma edge, in the steep gradient region, radiation transport effects must be taken into account. It is shown that due to these effects, the scrape-off layer region is not accessible to the ECEI measurements in steady state conditions and that the signal is dominated by the shine-through emission. Transient effects, such as filaments, can change the radiation transport locally, but cannot be distinguished from the shine-through. Local density measurements are essential for the correct interpretation of the electron cyclotron emission, since the density fluctuations influence the temperature measurements at the plasma edge. As an example, a low frequency 8 kHz mode, which causes 10%–15% fluctuations in the signal level of the ECEI, is analysed. The same mode has been measured with the lithium beam emission spectroscopy density diagnostic, and is very well correlated in time with high frequency magnetic fluctuations. With radiation transport modelling of the electron cyclotron radiation in the ECEI geometry, it is shown that the density contributes significantly to the radiation temperature ( T rad ) and the experimental observations have shown the amplitude modulation in both density and temperature measurements. The poloidal velocity of the low frequency mode measured by the ECEI is 3 km s –1 . The calculated velocity of the high frequency mode measured with the magnetic pick-up coils is about 25 km s –1 . Velocities are compared with the E  ×  B background flow velocity and possible explanations for the origin of the low frequency mode are discussed.